The Role of Digitalization in Improving the Performance of Accounting Information Systems in the Modern Era - Wafia Tamara; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the role of digitalization in improving the performance of accounting information systems in the modern era. The research employs a qualitative approach using library research by collecting and analyzing various relevant scientific literature. The findings indicate that digitalization plays a significant role in transforming accounting information systems from manual-based processes into more integrated, automated, and data-driven systems. This transformation enhances system performance through improved efficiency in work processes, increased accuracy of financial information, faster data processing, and more effective decision-making support. Furthermore, the study reveals that the success of digitalization implementation is influenced by several supporting factors, including human resource readiness, management support, and technological infrastructure. However, it is also constrained by inhibiting factors such as limited digital competencies, cybersecurity risks, and high implementation costs. Overall, the study concludes that digitalization serves as a strategic driver in improving accounting information system performance in the modern era characterized by rapid technological advancement and increasingly complex information demands.